Revealing Gender Inequality in Nissa Sabyan News Affair Videos Comment Space in Youtube: A Critical Discourse Study - Ayyatul Nisa Rahmadhani (English Language and Literature, 2020)
This study aims to reveal the gender inequality against Nissa Sabyan in news affair videos comment space in YouTube. The source of data are the bad comments written by netizens of Indonesia. The data in this study are in the form of words, phrases, and sentences that found in the comments section which contain gender inequality. Van Dijk’s theory is applied in this study. The result of this study shows that most of netizens in Indonesia only throw the bad comments which contain gender inequality against Nissa Sabyan by judging her appearance, giving her a bad label,insulting her for taking someone’s husband.